FIQH PERKAWINAN BEDA AGAMA SEBAGAI UPAYA HARMONISASI AGAMA (Studi Perkawinan Beda Agama di Kota Jember) - laela, ana; rozana, ken ismi; mutiah, Shilfa Khilwiyatul (FIKRAH, 2016)
The concept of interfaith marriage in terms of methods of content analysis and to read the harmonization of Religion. While Femenologis to read interfaith marriage in Jember City in an effort to harmonize religion .. This paper proposes to mengangkat concept of marriage as a religious difference harmonization religious people, there are three questions in this paper first, how the concept of Interfaith Marriage? second, how the concept of Interfaith Marriage Law in Indonesia? and thirdly how Practices Interfaith Marriage in Jember City in an effort to harmonize religious communities in the city of Jember? using the method of content analysis sebgai attempts to read the concept of interfaith marriage in Islamic law, and the law of Indonesia, while the approach femenologi as a method to look at the practice of interfaith marriage in the town of Jember, this study is the first to the concept of interfaith marriage, both the regions cacatan allowing civil mating different religions, and the third harmonization paraktek interfaith marriage in the town of Jember.Konsep Perkawinan beda agama ditinjau dari metode konten analisis dan untuk membaca harmonisasi Agama. Sedangkan Femenologis untuk membaca Perkawinan beda agama di Kota Jember sebagai upaya harmonisasi agama.. Paper ini ingin mengangkat konsep perkawinan Beda agama sebagai harmonisasi umat beragama, ada tiga pertanyaan dalam paper ini pertama,  bagaimana konsep Perkawinan Beda Agama ? kedua, bagimana konsep Perkawinan Beda Agama didalam Hukum Indonesia ? dan ketiga bagaimana Praktek Perkawinan Beda Agama di Kota Jember sebagai upaya harmonisasi umat beragama di Kota Jember ? dengan menggunakan metode konten analisis sebagai upaya membaca konsep perkawinan beda agama dalam hokum Islam, dan hokum Indonesia, sedangkan pendekatan femenologi sebagai metode untuk melihat praktek perkawinan beda agama di kota jember , hasil penelitian ini adalah pertama adanya konsep perkawinan beda agama, kedua adanya wilayah cacatan sipil yang memperbolehkan kawin beda agama, dan yang ketiga harmonisasi praktek perkawinan beda agama di kota jember.